Mouse Strain– and Charge-Dependent Vessel Permeability of Nanoparticles at the Lower Size Limit - Chen, Haoran; Liu, Yu-Cheng; Zhang, Zhiming; Li, Moxin; Du, Lidong; Wu, Pei-Chun; Chong, Wai-How; Ren, Fuzeng; Zheng, Weiming; Liu, Tzu-Ming (Frontiers in Chemistry, 2022)
Remarkable advancement has been made in the application of nanoparticles (NPs) for cancer therapy. Although NPs has been favorably delivered into tumors by taking advantage of the enhanced permeation and retention (EPR) effect, several physiological barriers presented within tumors tend to restrict the diffusion of NPs. To overcome this, one of the strategies is to design NPs that can reach the lower size limit to improve the ability of tumor penetration without being rapidly cleared by the body. Several attempts have been applied to achieve this, such as selecting appropriate nanocarriers and modifying surface properties. While many studies focus on the optimal design of NPs, the influence of mouse strains for the evaluation of NPs remains unknown. Therefore, this study aimed to assess whether the vascular permeability of NPs near the lower size limit differs among mouse strains. We found that the vessel permeability of dextran NPs was size-dependent and dextran NPs with size below 15nm exhibited leakage from postcapillary venules. Most importantly, the leakage of negatively charged FITC dextran at 8nm in diameter was significantly higher in BALB/c mouse strain than that in other strains. The difference in vascular permeability among mouse strains was not observed in neutral TRITC dextran with comparable sizes. Further study will be required to discover the mechanisms underlying the observed differences among mouse strains. Overall, our results indicate that the influence of mouse strain needs to be taken into account for the evaluation of NPs near the lower size limit.